Pengaruh Attitude Homophily, Social Attractiveness, Self-Disclosure, Endorser Credibility, dan Parasocial Interaction terhadap Purchase Intention - Kharisma, Fresha; Kurniawati, Masmira (Jurnal Ilmu Manajemen, 2021)
The increase in internet users encourages endorsers to market a product to shift to online media such as Youtube. The use of the online media Youtube by endorsers creates a unique attraction and can encourage consumers to make purchases. The purpose of this study is to determine the factors that need to be considered by marketers in marketing their products so that they can achieve a high level of consumer purchase intention. This research uses a quantitative survey method by distributing 210 questionnaires to Youtube viewers who have seen Atta Halilintar and know AHHA fashion products. Testing using structural equation models (SEM) shows the factors influencing consumer purchase intentions. The results show attitude homophily has a significant effect on endorser credibility. Attitude homophily, social attractiveness, and self-disclosure significantly affect parasocial interaction. Relationship with endorser credibility also has a significant impact on purchase intention. Social relationships have a significant effect on parasocial interactions. Interaction has a significant effect on Atta Halilintar's audience's purchase intention. This study implies that the endorsers who have the personality, credibility, and parasocial interactions that the audience likes will influence their purchase intention.